2014
DOI: 10.1371/journal.pone.0101764
|View full text |Cite
|
Sign up to set email alerts
|

Focal Radiation Therapy Combined with 4-1BB Activation and CTLA-4 Blockade Yields Long-Term Survival and a Protective Antigen-Specific Memory Response in a Murine Glioma Model

Abstract: BackgroundGlioblastoma (GBM) is the most common malignant brain tumor in adults and is associated with a poor prognosis. Cytotoxic T lymphocyte antigen -4 (CTLA-4) blocking antibodies have demonstrated an ability to generate robust antitumor immune responses against a variety of solid tumors. 4-1BB (CD137) is expressed by activated T lymphocytes and served as a co-stimulatory signal, which promotes cytotoxic function. Here, we evaluate a combination immunotherapy regimen involving 4-1BB activation, CTLA-4 bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
156
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 209 publications
(163 citation statements)
references
References 30 publications
5
156
1
1
Order By: Relevance
“…12 , 26 Based on these findings, we hypothesized that anti-PD-1 and anti-TIGIT dual therapy would be more effective than either monotherapy alone. However, there has been no established anti-TIGIT treatment schedule for GBM.…”
Section: Resultsmentioning
confidence: 99%
“…12 , 26 Based on these findings, we hypothesized that anti-PD-1 and anti-TIGIT dual therapy would be more effective than either monotherapy alone. However, there has been no established anti-TIGIT treatment schedule for GBM.…”
Section: Resultsmentioning
confidence: 99%
“…Studies were excluded because of following reasons: (1) not sufficient survival data reported, (2) letters, reviews, commentary, perspectives, case reports, conference abstracts, editorials or expert opinion, (3) studies reporting xenograft results in immunodeficient or humanized mice. Overall these search criteria helped short-list 15 research articles 12,15,16,[50][51][52][53][54][55][56][57][58][59][60][61] mentioned in Box S1.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, in a glioma model, the combination of RT plus CTLA-4 blockade significantly improved survival compared with untreated animals, whereas CTLA-4 blockade alone had no impact. 30 Furthermore, adding an agonist antibody to the costimulatory immune-checkpoint 4-1BB resulted in further improvement. The synergistic effect did not appear to depend on the timing of RT relative to drug therapy, Review Article and it is noteworthy that it appeared to be primarily CD4-positive T-cell mediated.…”
Section: Preclinical Rationale For Synergy Of Rt With Ctl-associated mentioning
confidence: 99%
“…The synergistic effect did not appear to depend on the timing of RT relative to drug therapy, Review Article and it is noteworthy that it appeared to be primarily CD4-positive T-cell mediated. 30 RT Synergy With Programmed Cell Death 1/Programmed Death-Ligand 1 Directed Therapy…”
Section: Preclinical Rationale For Synergy Of Rt With Ctl-associated mentioning
confidence: 99%